2001
DOI: 10.1103/physrevb.63.172405
|View full text |Cite
|
Sign up to set email alerts
|

Sign reversal of the orbital moment via ligand states

Abstract: It is demonstrated that the coupling between spin and orbital moments in magnetic systems may-for certain materials-be reversed from antiparallel to parallel, via the influence of ligand states. This is exemplified by first-principles calculations for an intermetallic compound VAu 4 , but the effect may be found also in other classes of materials. From a computational analysis of the influence of the ligand states, and from an expression based on perturbation theory, we show that ligand states, that traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
2
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 20 publications
2
30
2
2
Order By: Relevance
“…The large effect on the Mn orbital moment in the case of the 5d atoms has been already discussed in Ref. 30, where using perturbation theory it was shown that the large spin-orbit coupling of the 5d elements has a large effect on the orbital moment of the 3d neighboring atoms in the case of alloys.…”
Section: 29mentioning
confidence: 95%
See 1 more Smart Citation
“…The large effect on the Mn orbital moment in the case of the 5d atoms has been already discussed in Ref. 30, where using perturbation theory it was shown that the large spin-orbit coupling of the 5d elements has a large effect on the orbital moment of the 3d neighboring atoms in the case of alloys.…”
Section: 29mentioning
confidence: 95%
“…The latter rule, although derived for atoms, stands also for solids with few exceptions. 30 It states that if the d band is more than half-filled (Mn has 7 d-electrons) then the spin and orbital moments should be parallel. Increasing the valence of the X atom by one electron either following the 3d series (Fe→Co→Ni→Cu) or the 4d series (Rh→Pd→Ag) only scarcely changes the Mn orbital moment while there are significant variations in the value of the Mn spin moment.…”
Section: 29mentioning
confidence: 99%
“…29 They nicely described how the spin-orbit (SO) in Au may influence the orbit in V atoms through hybridization, provoking the reversal of its orbital moment and, therefore, the breakdown of the mentioned rule. Subsequent works on metallic compounds make use of this interpretation to demonstrate that the strong hybridization between the different atoms in the magnetic compounds is the key factor of such a breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…Only when the atomic character becomes appreciably modified due to strong hybridizations, the third Hund's rule might not be fulfilled, which is an exceptionally rare event. 32 The changes of the EDC's with the Cr concentration is accompanied by a change in magnetism: the Cr-rich alloys are antiferromagnetic, whereas CrPt 3 is ferrimagnetic ͑i.e., in the ordered phase, the Cr-Cr pairs couple ferromagnetically, while Cr-Pt pairs couple antiferromagnetically, as determined by neutron scattering 33,34 ͒. The weight of the hybridized states is strongly increased at the expense of the mainly Crderived states near the Fermi level.…”
Section: Resultsmentioning
confidence: 99%